Proximate composition and fatty acid profile of the myctophid Diaphus watasei Jordan & Starks, 1904 from the Arabian Sea - Manju, Sebastine; Kajal, Chakraborty; Bineesh, K. K.; Pillai, N. G. K.; Abdusamad, E. M.; Vijayan, K. K. (Indian Journal of Fisheries, 2011)
The edible portion of Diaphus watasei, a benthopelagic fish collected off Quilon, south-west coast of India was analysed for proximate composition and fatty acid profile. The fleshy part of the fish was found to contain 15.62% protein, 11.71% fat, 0.47% minerals, 0.28% soluble carbohydrate and 0.01% crude fibre. The dry matter in the fish was found to be about 28%. Monounsaturated fatty acids (MUFA) were found to have the highest (36.7%) share among total fatty acids followed by saturated fatty acids (SFA) (33.3%) and polyunsaturated fatty acids (PUFA) (25.5%). The abundant fatty acids were found to be oleic acid, palmitic acid, docosahexaenoic acid, stearic acid, myristic acid, linolenic acid, eicosapentaenoic acid and palmitoleic acid. The most predominant fatty acid was recorded as oleic acid which contributed 32% to the total fatty acids. Docosahexaenoic acid formed the single largest component of PUFA (9.33%) followed by Î³ linolenic acid (3.97%) and eicosapentaenoic acid (3.83%). The Ï‰-3 PUFA contributed about 70% of the total PUFAs. The most important Ï‰-3 PUFAs were EPA and DHA that contributed 73% to the total Ã¹ -3 polyunsaturated fatty acids.